2021
DOI: 10.1212/wnl.0000000000011697
|View full text |Cite
|
Sign up to set email alerts
|

Association of Digital Clock Drawing With PET Amyloid and Tau Pathology in Normal Older Adults

Abstract: ObjectiveTo determine whether a digital clock-drawing test, DCTclock, improves upon standard cognitive assessments for discriminating diagnostic groups and for detecting biomarker evidence of amyloid and tau pathology in clinically normal older adults (CN).MethodsParticipants from the Harvard Aging Brain Study and the PET laboratory at Massachusetts General Hospital were recruited to undergo the DCTclock, standard neuropsychological assessments including the Preclinical Alzheimer Cognitive Composite (PACC), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 33 publications
6
56
0
Order By: Relevance
“…The trends in their changes were consistent with those reported in previous studies on AD or MCI (for gait [7,8,27,33,42], for speech [19,31,[43][44][45][46][47], for drawing [22][23][24][25]). These behavioral sensitivities to the diagnosis of AD and MCI have been explained as follows: as these behaviors are complex tasks requiring coordination between widespread brain regions related to both motor and cognitive functions [12,13,24,27,29,[32][33][34][35][36], discrete characteristics of each behavioral modality may reflect neuropathological changes due to AD dementia [12,13,27,[56][57][58][59]. Our results align with those of previous studies that have shown statistically significant changes in behavioral characteristics from CN individuals and their larger changes in AD compared with earlier stages (i.e., MCI), suggesting the possibility of behavioral markers for detecting AD/MCI and neuropathological changes due to AD.…”
Section: Discussionmentioning
confidence: 99%
“…The trends in their changes were consistent with those reported in previous studies on AD or MCI (for gait [7,8,27,33,42], for speech [19,31,[43][44][45][46][47], for drawing [22][23][24][25]). These behavioral sensitivities to the diagnosis of AD and MCI have been explained as follows: as these behaviors are complex tasks requiring coordination between widespread brain regions related to both motor and cognitive functions [12,13,24,27,29,[32][33][34][35][36], discrete characteristics of each behavioral modality may reflect neuropathological changes due to AD dementia [12,13,27,[56][57][58][59]. Our results align with those of previous studies that have shown statistically significant changes in behavioral characteristics from CN individuals and their larger changes in AD compared with earlier stages (i.e., MCI), suggesting the possibility of behavioral markers for detecting AD/MCI and neuropathological changes due to AD.…”
Section: Discussionmentioning
confidence: 99%
“…Future plans include biomarkers studies focusing on measuring the association of DCTclock metrics with PET amyloid and tau. In fact, one such validation study comparing DCTclock to PET global amyloid, PET global tau, and the A4 Preclinical Alzheimer Cognitive Composite (PACC) has already obtained interesting results (15), showing that DCTclock performance was strongly associated with both amyloid and tau deposition in both unimpaired and subtly impaired individuals as measured by the PACC, and also correlated well with the PACC. Thus, we believe that this novel integrative model of clinician, artificial intelligence, and technology provide exciting opportunities for scientific advancement in the understanding cognitive change that may occur in early stage neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We describe how the algorithms were developed, the resulting clinical scores, and the validation findings based on comparisons between AD and aMCI clinical samples and a community-based normal aging population. A separate validation study of this technology in pre-clinical AD individuals has already shown that DCTclock is strongly correlated with tau and amyloid loads on PET (15). DCTclock is FDA-cleared to market as a computerized cognitive assessment aid, offering a sensitive and scalable early detection method for cognitive health and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…An analogous tool for Alzheimer's disease screening, the DCTclock test TM , has demonstrated the feasibility of designing and implementing digital drawing tasks in clinical settings to assess areas of cognitive state. The DCTclock TM test has demonstrated clinically significant associations for Alzheimer's disease biomarkers as well as strong capabilities for discriminating between cognitively healthy individuals and patients with mild cognitive impairment or early Alzheimer's dementia [18]. Passing clinical trials and receiving FDA clearance, the successful deployment of this tool speaks to the feasibility of a similar approach to PD screening as well as the readiness of modern clinical settings to incorporate these digitized methods.…”
Section: Handwriting Analysis For Parkinson's Diseasementioning
confidence: 99%